2022
DOI: 10.5897/ajbm2021.9335
|View full text |Cite
|
Sign up to set email alerts
|

Marketing strategies and consumers purchasing behaviour in Ghana: A case of Nestle Ghana Limited

Abstract: The role marketing strategies plays in influencing purchasing behaviors of consumers in various economies can never be overemphasized. However, this assertion requires further investigation with respect to consumers of Maggi seasoning products in Ghana especially those in Tamale metropolis. The study analyzed the effect of marketing strategies specifically sales promotion and perceived product quality on consumers' purchasing behavior toward Maggi products in the Tamale metropolis of Ghana. To achieve this goa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 44 publications
(31 reference statements)
0
1
0
Order By: Relevance
“…In relation to retail product purchase intention, perceived product quality has a significant influence on consumer purchase intention [7], [8]. The perceived quality product is also a key marketing strategy and can play an important role in explaining any change in consumer buying behavior [9]. Although many studies consider perceived product quality very important in building purchase intention, but Kitburin and Methavasaraphak [10] found that perceived product quality had the lowest influence on purchase intention.…”
mentioning
confidence: 99%
“…In relation to retail product purchase intention, perceived product quality has a significant influence on consumer purchase intention [7], [8]. The perceived quality product is also a key marketing strategy and can play an important role in explaining any change in consumer buying behavior [9]. Although many studies consider perceived product quality very important in building purchase intention, but Kitburin and Methavasaraphak [10] found that perceived product quality had the lowest influence on purchase intention.…”
mentioning
confidence: 99%